SERVICE QUALITY AND POSITIVE WOM INCREASING CUSTOMER SATISFACTION: PURCHASING DECISION AS INTERVENING VARIABLE - Dwi Syafitri, Shifa; MH Nainggolan, Bonifasius (Management and Leadership Study Programme, 2023)
This study examines the service quality of Bakso Rusuk Joss restaurant in Depok and Positive WOM for customer satisfaction through purchasing decisions. As part of the research survey methodology, questionnaires were sent to restaurant customers. The final data sample was obtained on Bakso Rusuk Joss with 245 respondents who made purchases twice or more. Hypothesis testing was carried out using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. PLS-SEM analysis is carried out in two steps. The first step is the reliability and validity analysis, while the second step is the estimation and verification of path coefficients and performance of structural models. Hypothesis testing with SEM using PLS-SEM 2.3.9 software. The results of this study show that service quality has a direct positive and significant effect on customer satisfaction and purchasing decisions. Positive WOM has a direct and significant impact on customer satisfaction. Purchase decisions have a direct and significant impact on customer satisfaction.